A Politeness Strategies in EFL Interaction of Indonesian Students and Lectures - Putri Nila Sudewi, Ni Ketut; Suktiningsih, Wiya; Muhlisin, Muhlisin; Widani, Ni Nyoman (Asosiasi dosen IDEBAHASA KEPRI, 2023)
A Through language, we can see someone’s behaviour from their way of speaking. The way speakers behave well can be achieved by paying attention to important aspects of communication; this is called the politeness strategy. The purpose of this study is to investigate the politeness strategies in the ELF interaction of Indonesian students—lecturers both online and offline in the classroom. This study aimed to collect, analyse, and interpret the data that was collected through the WhatsApp application and student-lecturer interaction in the classroom. A descriptive-qualitative method was used to find out the politeness strategy used in EFL interactions with Indonesian students and lecturers. There were four politeness strategies used by students and lecturers, such as the positive politeness strategy, the negative politeness strategy, the bald on record strategy, and the off-record strategy. The positive politeness strategy was found to be the most frequent strategy used in student and lecturer interaction in WhatsApp groups and classrooms. The most frequent strategies used by students and lecturers in their interaction were politeness strategies such as greetings, using in-group identity markers, seeking an agreement, offering promises, being optimistic, and giving gifts.